The Professional Socialization of Early Career Medical Laboratory Scientists. - SCHILL, JANNA (Clinical Laboratory Science)
The medical laboratory science profession has faced more than twenty-years of a workforce shortage. One component that plays a role in the workforce shortage is the attrition of early career medical laboratory scientists shortly after graduation from an accredited medical laboratory science educational program. This study seeks to identify factors that contribute to the professional socialization of early career clinical laboratory scientists. In this study early career medical laboratory scientists' express high levels of professional behaviors and attitudes coupled with a strong professional identity necessary to remain in the medical laboratory science profession. In addition, this study identified the presence of a theorypractice transition gap that may contribute to retention and attrition of new professional's as they transition from the classroom into the medical laboratory workforce.